Comprehensive ADP‐ribosylome analysis identifies tyrosine as an ADP‐ribose acceptor site. (28th June 2018) - Leslie Pedrioli, Deena M; Leutert, Mario; Bilan, Vera; Nowak, Kathrin; Gunasekera, Kapila; Ferrari, Elena; Imhof, Ralph; Malmström, Lars; Hottiger, Michael O
Abstract: Despite recent mass spectrometry (MS)‐based breakthroughs, comprehensive ADP‐ribose (ADPr)‐acceptor amino acid identification and ADPr‐site localization remain challenging. Here, we report the establishment of an unbiased, multistep ADP‐ribosylome data analysis workflow that led to the identification of tyrosine as a novel ARTD1/PARP1‐dependent in vivo ADPr‐acceptor amino acid. MS analyses of in vitro ADP‐ribosylated proteins confirmed tyrosine as an ADPr‐acceptor amino acid in RPS3A (Y155) and HPF1 (Y238) and demonstrated that trans ‐modification of RPS3A is dependent on HPF1. We provide an ADPr‐site Localization Spectra Database (ADPr‐LSD), which contains 288 high‐quality ADPr‐modified peptide spectra, to serve as ADPr spectral references for correct ADPr‐site localizations. Synopsis: Despite recent mass spectrometry‐based breakthroughs, accurate ADP‐ribose‐site localization remains challenging. Here the authors developed an unbiased, multistep ADP‐ribosylome data analysis workflow that identified tyrosine as a novel in vivo ADPr‐acceptor amino acid. Identification of tyrosine as a novel ARTD1/PARP1‐dependent ADPr‐acceptor amino acid in vivo and in vitro . ARTD1‐mediated tyrosine ADP‐ribosylation is dependent on HPF1. Quantitative MS analysis reveals that ARTD1/PARP1 is the main ADP‐ribosyltransferase activated in vivo upon H2 O2 treatment and that it modifies different proteins compared to ARTD2/PARP2. Establishment and delivery of an ADP‐ribose‐site Localization Spectra Database (ADPr‐LSD) as reference and training tool. Abstract : Despite recent mass spectrometry‐based breakthroughs, accurate ADP‐ribose‐site localization remains challenging. Here the authors developed an unbiased, multistep ADP‐ribosylome data analysis workflow that identified tyrosine as a novel in vivo ADPr‐acceptor amino acid.